PENGEMBANGAN BOOKLET KAJIAN STRUKTUR POPULASI TUMBUHAN MENTEGA (Diospyros blancoi) DI KAWASAN DESA SUNGAI LANDAS SEBAGAI BAHAN PENGAYAAN KONSEP SUB PLANTAE BIOLOGI SMA - Aminah, Siti; Mahrudin, Mahrudin; Rezeki, Amalia (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
Education in the 21st century requires teachers to demonstrate creativity by developing innovative learning resources, particularly in biology education. One form of printed teaching material that can be developed is a booklet, which offers visual appeal through illustrations, colors, and concise text. A booklet highlighting the local potential of the butter plant (Diospyros blancoi) is expected to serve as enrichment material for students, especially related to the Sub-Plantae concept. This study aims to (1) describe the population structure of Diospyros blancoi in the Sungai Landas Village area and (2) evaluate the feasibility of a booklet titled “Getting to Know Butter Plants in the Sungai Landas Village Area as Enrichment Material for High School Biology.” The booklet development followed the Plomp model, which includes five phases: preliminary investigation, design, realization/construction, testing, evaluation and revision, and implementation. The evaluation phase applied Tessmer’s formative evaluation approach. Population structure data were obtained by categorizing plants into three age phases: pre-reproductive, reproductive, and post-reproductive. The results showed that the number of pre-reproductive individuals was 6, reproductive 18, and post-reproductive 11. The density of each phase was 1.25 ind/ha (pre-reproductive), 3.75 ind/ha (reproductive), and 2.29 ind/ha (post-reproductive). The population exhibited a disturbed pyramid structure, indicating a potential decline in adult individuals in the future. The validity test yielded a score of 83.85% (valid), while the content practicality test scored 96.61% (very good) and the expected practicality test scored 97% (very good). Based on these results, the developed booklet is categorized as valid and practical, making it suitable for use as an enrichment material in high school biology learning.